Stem diameter and height of chrysanthemum cv Yokoono as affected by gibberellic acid - da Silva Vieira, Marcos Ribeiro [UNESP]; de Souza, Angela Vacaro [UNESP]; Guimaraes Santos, Caio Marcio [UNESP]; Alves, Leonardo de Sousa; Cerqueira, Reginaldo Conceicao [UNESP]; Paes, Reinaldo de Alencar; de Souza, Aline Danielle; de Sousa Fernandes, Luiza Maria [UNESP] (Academic Journals, 2011)
The effect of gibberellic acid has been shown mainly to promote cell division and elongation. This study was aimed to evaluate the development of height and diameter of the stems of chrysanthemum cultivar Yoko ono by the applications of gibberellic acid (GA(3)) in the field. The treatments were composed of four doses (0, 40, 80 and 120 mg L(-1)) at 15 and 30 days after transplanting. From the findings, It can be concluded that GA(3) significantly affected the diameter of stem at higher doses, and was unable to affect the height of stem.
Keywords: Dendranthema grandiflora; flowers; plant regulator; concentration